Overview Basic Sanitation In Payaman Village, Bojonegoro District 2016 - Almas Ghassani Celesta; Nurul Fitriyah (Universitas Airlangga, 2019)
Facilities of basic sanitation have three very important components, clean water supply, household waste disposal and healthy water closet. The aim of this study was provided a comprehensive picture of basic sanitation as an effort in a village environmental sanitation. This research was an observational research. The study was conducted in Payaman Village, Kecamatan Ngraho, Bojonegoro District, East Java Province. The technique of sampling using cluster sampling so that the sample are all Merbong and Ketawang hamlet in RT 8-14, RW 2-4 consisted of 248 Head of Family (KK). Primary data methods using indepth interview and observation. Data processing is done descriptively. From the results of the study, 99,6% of households already have clean water supply, but there are still 79,0% of families who do not have the appropriate SPAL. Then there are still 67.7% of families who have not provided a garbage disposal facility at home, and 94.4% KK management their garbage with burning on premises. There are still 10,1% of families who do not have healthy water closet at home. The recommendation given to the residents is the motivation for the availability of latrines and SPAL and the socialization of waste management.